2012
DOI: 10.1371/journal.pntd.0001556
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity in Oral Samples of Children in Niger with Acute Noma, Acute Necrotizing Gingivitis, and Healthy Controls

Abstract: BackgroundNoma is a gangrenous disease that leads to severe disfigurement of the face with high morbidity and mortality, but its etiology remains unknown. Young children in developing countries are almost exclusively affected. The purpose of the study was to record and compare bacterial diversity in oral samples from children with or without acute noma or acute necrotizing gingivitis from a defined geographical region in Niger by culture-independent molecular methods.Methods and Principal FindingsGingival samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 33 publications
(48 reference statements)
2
64
0
4
Order By: Relevance
“…18 & Bolivar et al 19 identified prevotella intermedia and peptostreptococus to be more clearly associated with noma. As it has a multifactorial etiology, additional studies are warranted to clarify its exact microbiology.…”
mentioning
confidence: 97%
“…18 & Bolivar et al 19 identified prevotella intermedia and peptostreptococus to be more clearly associated with noma. As it has a multifactorial etiology, additional studies are warranted to clarify its exact microbiology.…”
mentioning
confidence: 97%
“…revotella intermedia is a black-pigmented anaerobic Gramnegative bacterium which has long been known to be associated with oral diseases, such as chronic periodontitis (1-3), aggressive periodontitis (4-6), puberty-associated gingivitis, acute necrotizing ulcerative gingivitis (7,8), periapical periodontitis (9,10), and noma (an acute gangrenous disease) (11,12). Besides being involved in oral diseases, P. intermedia has also been reported to be associated with various systemic diseases, such as cystic fibrosis, chronic bronchitis (13)(14)(15), and atherosclerosis (16).…”
mentioning
confidence: 99%
“…Our results suggest that as long as P. intermedia is present, all species can survive and the infections can persist. P. intermedia is also associated with the severe oral infections necrotizing gingivitis and noma (54) and with several other polymicrobial infections, including diabetic foot ulcers (55) and bacterial vaginosis (56), and is found in lungs of cystic fibrosis patients (57). It is possible that the cytotoxic activity we have described may be important in these other infections as well.…”
Section: Discussionmentioning
confidence: 89%